2020
DOI: 10.1016/j.celrep.2020.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem and Stromal Cells Harness Macrophage-Derived Amphiregulin to Maintain Tissue Homeostasis

Abstract: Highlights d MSCs enhance macrophage phagocytosis through MSC mitochondria-containing vesicles d MSCs elicit secretion and transcription of amphiregulin in macrophages d Amphiregulin secretion depends on macrophage phagocytosis and MSC vesicle uptake d Macrophage amphiregulin increases Treg cells and preserves epithelial stem cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 72 publications
4
70
0
Order By: Relevance
“…AREG or amphiregulin is an Epidermal Growth Factor (EGF)-like molecule that has recently been shown to play a central role in orchestrating both host resistance to pathogens and immune tolerance mechanisms [ 46 , 47 , 48 ]. This cross-talk between immune cells (such as macrophages) and epithelial cells are programmed to promote inflammation resolution and tissue regeneration, leading to homeostasis after injury [ 49 ]. However, with a chronic persistent inflammatory stimulus such as cigarette smoking, it could promote proliferation of structural cells such as fibroblasts and their production of pro-inflammatory cytokines such as IL-8, vascular endothelial growth factor (VEGF), and transforming growth factor alpha (TGF-α) with augmented expression in chronic inflammatory conditions such as rheumatoid arthritis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…AREG or amphiregulin is an Epidermal Growth Factor (EGF)-like molecule that has recently been shown to play a central role in orchestrating both host resistance to pathogens and immune tolerance mechanisms [ 46 , 47 , 48 ]. This cross-talk between immune cells (such as macrophages) and epithelial cells are programmed to promote inflammation resolution and tissue regeneration, leading to homeostasis after injury [ 49 ]. However, with a chronic persistent inflammatory stimulus such as cigarette smoking, it could promote proliferation of structural cells such as fibroblasts and their production of pro-inflammatory cytokines such as IL-8, vascular endothelial growth factor (VEGF), and transforming growth factor alpha (TGF-α) with augmented expression in chronic inflammatory conditions such as rheumatoid arthritis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, we performed RNA sequencing on the MSCs and compared the transcriptome of miR-146a inhibitor-MSCs with that of NC-MSCs ( Figure 2 B). In particular, we analyzed the immune response- and secretion-related genes, because MSCs control immune responses largely through the secretion of paracrine factors [ 5 , 6 , 7 ]. The data revealed that 10 genes were upregulated >three-fold and six genes downregulated >three-fold in miR-146a inhibitor-MSCs, compared to NC-MSCs ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…The data revealed that 10 genes were upregulated >three-fold and six genes downregulated >three-fold in miR-146a inhibitor-MSCs, compared to NC-MSCs ( Figure 2 B). The upregulated genes included pentraxin 3 (PTX3), tumor necrosis factor-inducible gene 6 (TSG-6), and cyclooxygenase-2 (COX-2), which are well-known to mediate the immunomodulatory actions of MSCs [ 7 , 8 , 9 , 10 , 11 , 12 ]. Meanwhile, hepatocyte growth factor (HGF) and stanniocalcin 1 (STC-1), other therapeutic factors expressed by MSCs [ 13 , 14 , 15 ], were among the downregulated genes in miR-146a inhibitor-MSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MSCs have been demonstrated to harness macrophage derived amphiregulin (AREG) to maintain tissue homeostasis after injury. By increasing the secretion of AREG in a phagocytosis-dependent manner, MSC-primed macrophages allowed immunosuppression through the promotion of regulatory T (Treg) ( Ko et al, 2020 ).…”
Section: Cell Death As a Component Of Msc Immunomodulatory Propertiesmentioning
confidence: 99%